The Role of the Principal as a Motivator at SMAN 2 Bulukumba - Alim, Muh Alfurqan Alim; Irmawati Irmawati; Sitti Habibah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study examines the role of the principal as a motivator at SMAN 2 Bulukumba using a descriptive qualitative approach. Data were collected through observations, interviews, and documentation, with the principal and teachers as the main sources. The findings reveal that the principal plays an active role in motivating by managing the physical environment, ensuring adequate facilities and infrastructure, as well as maintaining school safety and cleanliness. In fostering teacher discipline, the principal applies persuasive approaches, role modeling, structured guidance, and open communication. Furthermore, the principal designs fair and inclusive reward programs, which enhance teacher motivation, work enthusiasm, and professionalism. Supporting factors include the creation of a conducive school environment, harmonious cooperation, open communication, and wise leadership. Meanwhile, the inhibiting factors consist of the lack of active participation from some teachers and staff, as well as limited facilities and infrastructure, which hinder the optimal implementation of motivational programs..